Pemeriksaan Hitung Jenis Sel Monosit Pada Penderita Tuberkulosis Paru di Rumah Sakit Khusus Paru Medan - Yuswardi W, Dicky; Denrison Purba; Hafifah Syahpadilla (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2023)
Tuberculosis is an infectious disease caused by the bacteria Mycobacterium tuberculosis with a percentage of 80% that most often occurs in the lungs. Transmission of TB itself can be through droplets of sputum when coughing or sneezing and can infect other healthy people. Diagnosis of TB is based on history and physical examination as well as other supporting examinations, namely radiological and bacteriological examinations. Monocytes are the largest leukocyte cell type. Its cell nucleus has fine chromatin granules that bend in the shape of a kidney/mung bean seed. Monocytes have two functions, namely as phagocytes of microorganisms (especially fungi and bacteria) and other foreign bodies, and play a role in immune reactions. This type of research is descriptive which aims to determine the percentage of monocyte cells in patients with pulmonary tuberculosis. This research was conducted in June-July 2023 at the Pulmonary Specialized Hospital with a sample of 10 people. Based on the results of the study, the number of monocytes increased by 6 people (60%) and normal by 4 people (40%). Increased monocyte counts can occur because they have not received or have not completed initial treatment for 2 months. Normal monocyte cells are due to having received treatment for 2 months. Suggestions for patients with pulmonary tuberculosis both who have and have not received 2 months of treatment should continue with 6 months of treatment and conduct periodic inspection.